REVIEW TERHADAP PUTUSAN MAHKAMAH KONSTITUSI TENTANG STATUS ANAK DI LUAR NIKAH - A Zamakhsyari Baharuddin (Al-'Adl, 2019)
Indonesia was astonished by the Constitutional Court ruling relating to the status of a child outside of a legal marriage. Although it is considered not the main intention of the Constitutional Court members to legalize adultery, many people predict this will lead to many wrong interpretations and lead to the opening of very wide space to the practice of adultery. The main reason behind the verdict was to protect the status of children born out of legitimate marriages and their human rights because in truth they did not know what caused them to lose the rights that normal children should have. born into a legal marriage, and what befalls them is not in their power, but in their parents. So, if there is revocation of the right to a certain act, their parents' rights must be revoked. Muslims who are very opposed to the practice of adultery, and matters relating to it, driven by the scholars who are concerned with the verdict, raise their voices with their voices to reject decision No. 46 / PUU-VIII / 2010. Based on the principle of sadd-adz-dzari'ah, the majority of Muslims firmly reject the ruling, based on the aim of closing meetings for opportunities for the spread of adultery practices.